Aktivitas Pariwisata Pulau Dutungan Desa Cilellang Kecamatan Mallusetasi Kabupaten Barru - Ardeni; Darman Manda (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine the precession of the community towards the natural environment, especially in tourism activities, to determine the influence of the Dutungan Island tourist attraction on the economic development of the community, to provide an overview of the community's efforts to protect the environment of the Dutungan Island tourist attraction, and to describe the efforts of the community and local government in introducing Dutungan Island tourism object to become sustainable tourism. To achieve this goal, a qualitative research method was adopted by means of observation, interviews and documentation. The data obtained is then analyzed and interpreted based on relevant theories and research results. The results of this show that the relationship between humans and the natural environment in tourism activities on the Dutungan Island tourist attraction is very important. The existence of tourist objects has an influence on the community's economy as well as the presence of a harmonious community and continues to preserve the environment by carrying out nature-loving activities. Until now, the community's culture of protecting the environment is still maintained so that it can maintain natural resources and produce several ecosystems that are utilized by the community and used as a livelihood